Studien zur Systematik und Taxonomie der Gattung Hylaeus F. (4) Hylaeus sinensis sp. n. - Nachweis der montan-disjunkten Verbreitung einer Artengruppe um Hylaeus niger Bridwell (Apidae, Colletinae). - Dathe, Holger H. (Contributions to Entomology = Beiträge zur Entomologie, 2005)
Hylaeus sinensis sp. n., found in the south-eastern Himalaya near the Chinese border with Myanmar, is closely related only to H. niger Bridwell, 1919 from Japan. Both species obviously belong to a species group with extensive montane-disjunct distribution as is known in a very similar pattern in some beetle species. A subgeneric separation (Nesohylaeus Ikudome, 1989) is discussed.KeywordsHymenoptera, Apidae, Colletinae, Hylaeus, new species, montane species, Himalaya, China, Japan.Nomenclatural Actssinensis Dathe, 2005 (Hylaeus (Hylaeus)), spec. n.